2011
DOI: 10.5535/arm.2011.35.5.673
|View full text |Cite
|
Sign up to set email alerts
|

The Availability of Radiological Measurement of Tibial Torsion: Three-Dimensional Computed Tomography Reconstruction

Abstract: ObjectiveTo assess the intra-rater and inter-rater reliability for measuring tibial torsion measurements by a radiographic method using three-dimensional computed tomography reconstruction (3D-CT) and to compare the physical measures to those of 3D-CT.MethodThe study included 33 children who presented with intoeing gait. Tibial torsion was measured by 3D-CT. Distal reference point was the bimalleolar axis. Proximal reference points were the transtibial axis and posterior condylar axis. Physical measurements in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…1,2,21 Although there have been attempts to quantify both tibial torsion and femoral anteversion on computed tomography and other advanced imaging, these techniques are not a common part of most practitioner's workup because they offer lower interrelator reliability than physical examination and introduce unnecessary testing. 1,7,8,[11][12][13][14][22][23][24][25][26][27][28][29] Treatment practices vary widely regarding the surgical management of these conditions. At our institution patients may be considered for a derotational osteotomy if they are symptomatic and have notable deformity beyond age 6 years for tibial torsion and 8 years for femoral anteversion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,21 Although there have been attempts to quantify both tibial torsion and femoral anteversion on computed tomography and other advanced imaging, these techniques are not a common part of most practitioner's workup because they offer lower interrelator reliability than physical examination and introduce unnecessary testing. 1,7,8,[11][12][13][14][22][23][24][25][26][27][28][29] Treatment practices vary widely regarding the surgical management of these conditions. At our institution patients may be considered for a derotational osteotomy if they are symptomatic and have notable deformity beyond age 6 years for tibial torsion and 8 years for femoral anteversion.…”
Section: Discussionmentioning
confidence: 99%
“…This introduces a similar problem found in radiographic studies; however, other authors using similar bony landmarks found excellent correlations with physical examination findings. 8,12,14,24,36 In addition, manipulating the bones in-hand allowed for precise localization and positioning of specimens that was not limited to the orthogonal planes in reformatted computed tomographic scans. The cadaveric skeletons used in this study were devoid of articular cartilage; we were thus unable to assess degenerative joint disease at this location.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability and reproducibility of two-dimensional CT scans are limited by anatomical determination, especially along the femoral neck axis (7,8), and by positional variables that influence the accuracy of measurement (9). 3D CT reconstruction enables the precise determination of femoral and tibial torsion without influence from femoral or tibial positioning and the determination of femoral neck axis (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…In human medicine, different diagnostic approaches such as clinical examination, 16,21 radiography, 13,22 computed tomography (CT), 12,[23][24][25] ultrasound, 26 and fluoroscopy 15,27 have been described for assessing TT. The accuracy of radiography 18 and CT 28 have been investigated in the first reports in veterinary medicine focusing on TT.…”
Section: Introductionmentioning
confidence: 99%